Remembering and forgetting floods and droughts: lessons from the Welsh colony in Patagonia. (April 2021) - Griffiths, Hywel M; Tooth, Stephen
Sustainable flood memories – defined as those formed of folk memories of flooding, flood heritage and other local, lay knowledges – have been identified as having great potential for increasing community resilience to floods. Focusing on the social and cultural aspects of flood and drought memory, we present the findings of archival research, interviews with residents of the Welsh colony in Argentine Patagonia ( Y Wladfa in Welsh), and critical textual analysis of museum spaces. This analysis enables reconstruction of flood and drought history over the 150 years of the colony, provides insights into the impact, emotive power and perception of floods and droughts, and highlights the ways in which lay knowledge and flood and drought memories are transmitted vertically and shared horizontally in material and immaterial ways. We argue that specific thresholds of memory exist, as related to flood/drought magnitude, duration, social impact and memorialisation, which ensure that some events are encoded, transcribed and transmitted through the collective memoria of a community, while other events may fade from memory. Ensuring long-term sustainability of the Welsh-language community, and integration of these flood/drought memories with those from other cultures and languages, will help develop community resilience to 21 st century hydroclimatic changes.